Last problem before the Lunar New Year! - Minimalism is a decision - (7)

Algebra Level 3

{ x = a b c = a + b + c a b + b c + c a = 1 a ( b 2 + c 2 ) + b ( c 2 + a 2 ) + c ( a 2 + b 2 ) = \large \left \{ \begin{aligned} x &= abc = a + b + c\\ &ab + bc + ca = 1 \end{aligned} \right. \implies a(b^2 + c^2) + b(c^2 + a^2) + c(a^2 + b^2) = \square

What is \square ?

2 x 2x 2 x -2x 2 -2 x -x 0 0 1 -1 x x 1 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Atomsky Jahid
Feb 4, 2019

a ( b 2 + c 2 ) + b ( c 2 + a 2 ) + c ( a 2 + b 2 ) a(b^2+c^2)+b(c^2+a^2)+c(a^2+b^2) = a b ( a + b ) + b c ( b + c ) + c a ( c + a ) =ab(a+b)+bc(b+c)+ca(c+a) = a b ( x c ) + b c ( x a ) + c a ( x b ) =ab(x-c)+bc(x-a)+ca(x-b) = x ( a b + b c + c a ) 3 a b c =x(ab+bc+ca)-3abc = 2 x =-2x

Yeah, it's that easy. Happy Lunar New Year!

Thành Đạt Lê - 2 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...